Lower Lip Reconstruction Revisited: Technical Solutions to Prevent Oral Incontinence and Maximize Vermilion Anterior Projection. Issue 4 (October 2020) - Lee, Lauren P.; Karagiannis, Phaeton; Kim, Doveen; Thompson, John F.; Saw, Robyn; Lee, Kenneth K.; Ch'ng, Sydney
Abstract : Supplemental Digital Content is available in the text.